Fandom tribe: the depiction of gender inside Good Omens fanfiction - Girardi, Thalia Ester de Candido (My University, 2019)
Sharing and creating stories is one of our main characteristics as humans. Creating fanfiction is one of the results of this story-telling tradition. Fanfiction is usually done by members of a determined fandom, which is a community united by the love for a determined piece of media. This community behavior is what Maffesoli named tribalization. This process is very clear inside the Good Omens fandom, which is very peculiar when dealing with the notion of sex and gender. It is like this because of the fluidity of these concepts when talking about supernatural beings, who do not really fit inside the traditional binary notion of what constitutes men and women. This makes Good Omens fandom especially good at subverting gender expectations and depictions. This work investigates the representation of genders inside Good Omens' fanfiction (sic).
Compartilhar e criar histórias é uma das nossas principais características como seres humanos. Criar fanfiction é um dos resultados dessa tradição de contação de histórias. A fanfiction geralmente é feita por membros de um determinado fandom, que é uma comunidade unida pelo amor por uma determinada obra midiática. Esse comportamento de comunidade é o que Maffesoli chama de tribalização. Esse processo está muito claro no fandom de Good Omens, que é bem peculiar ao lidar com a noção de sexo e gênero. É assim por causa da fluidez desses conceitos quando falamos de seres sobrenaturais, que não se encaixam realmente na noção binária tradicional do que constitui homens e mulheres. Isso torna o fandom de Good Omens especialmente bom em subverter as expectativas e representações de gênero. Este trabalho investiga a representação de gêneros dentro das fanfictions de Good Omens (sic).
Keywords: Fan fiction; Gender identity in literature; Identity (Psychology)